ENHANCING MENTORSHIP IN THE PRACTICUM: IMPROVING CONTEXTUAL SUPERVISION - Ralph, Edwin G. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2003)
ABSTRACT. This report describes a project that enacted recent changes to the implementation of the Contextual Supervision (CS) model with two cohorts of classroom cooperating teachers (CCTS) and their teacher-interns in an extended-practicum program in Western Canada. When compared to the results of previous research on CS, the findings from the current study reveal a distinct improvement in the appropriate matching of cooperating teachers' mentorship styles with their teacher-interns' skill-specific developmental levels in teaching. Reasons for this improvement are presented, and implications for practicum organizers are drawn. POUR FAVORISER LE MENTORAT DURANT LES STAGES PRATIQUES: L'AMÉLIORATION DES SUPERVISIONS CONTEXTUELLES RÉSUMÉ. Cet article décrit la mise en place de récents changements dans l'implantation du modèle de supervision contextuelle (SC) auprès de deux groupes de maîtres associés et de leurs stagiaires lors d'un stage de longue durée dans l'ouest canadien. Lorsque les résultats de cette présente étude sont comparés aux recherche antérieures portant sur la supervision contextuelle, les conclusions révèlent une amélioration appréciable dans l'appariement du style de mentorat des maîtres associés et du degré de développement des habiletés pédagogiques du stagiaire. Les raisons de cette amélioration sont présentées ainsi que leurs implications dans la planification des stages pratiques.